Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Evaluate -2x+6y when x= -3 y=-1

Sagot :

LC447

Answer:

0

Step-by-step explanation:

Substitute x for -3 and y for -1:

= -2(-3) + 6(-1)

= 6 + -6 (or 6 - 6)

= 0